Ice hockey officiating retention: a qualitative understanding of junior ice hockey officials' motivations in Canada. Issue 1 (4th May 2019) - Fowler, Brian; Smith, Jimmy; Nordstrom, Heidi; Ferguson, Tyler
ABSTRACT: An 8% annual growth internationally in registered ice hockey players has spurred the need for more officials. Understanding long-term motivations of these officials can help with retention. The present study utilized self-determination theory (SDT) to examine the motivations of ice hockey officials who continue in the officiating profession. A qualitative analysis of 15 semi-structured interviews of officials in the Ontario Hockey Association (OHA) was employed to gain understanding of ice hockey official motivations. Five emerging themes were uncovered to explain these motivations: (1) family, (2) new perspective, (3) comradery, (4) advancement, and (5) commitment and dedication. The current research attempted to fill a gap in the literature regarding official motivations and retention, as conversely, previous scholars have focused on factors of why officials quit. These findings may be helpful to sport organizations in understanding motivations of officials, so they can then cater to these motivations, and possibly increase retention.